Study of Comfort Temperature for Bowling Activity at Bowling Centre of Batu Pahat Pacific Mall - YEO, YEO HAN YONG; Idris, AHMAD FU'AD (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The objective of this study is to predict the comfort temperature for bowling activities at bowling centre of Batu Pahat Pacific Mall. There are two types of methods for data collection in this study, which are physical measurement and human response methods. For physical measurement, it consisted of four environmental parameters that measured by the instruments VelociCalc® Plus device and KIMO® AMI 310 device, and two personal parameters are calculated through observation. While, human response method is based on the survey form. After the full data collection, the PMV values are calculated from each method. The relationship between air temperature and PMV value was predicted using correlation and regression analysis. Three different trend line equation of air temperature against predicted mean vote (PMV) was developed through SPSS software, and the equation which shows strongest relationship is chosen to predict the comfort temperature based on ASHRAE 55. Based on the result of correlation and regression analysis, the cubic polynomial equation was chosen to determine the range of comfort temperature for bowling activity because it has the highest correlation and regression coefficient. The cubic polynomial equation of physical measurement and human response methods was y = -3.1447 x3 + 1.025 x2 + 4.3334 x + 24.102 and y = -1.0399 x3 + 1.4269 x2 + 3.4184 x + 23.827 respectively. The minimum and maximum comfort temperature for physical measurement was 22.58℃ and 26.13℃ respectively, whereas the minimum and maximum comfort temperature for human response was 22.61℃ and 25.76℃ respectively. Based on the result obtained, the range of comfort temperature of Batu Pahat Pacific Mall bowling centre was acceptable because it was just slightly different with the ASHRAE Standard 55 (23.0℃ to 26.0℃).